Anacleta's Vine (2011)
"Anacleta has found a seed, sowed it in the garden, and now he looks at it. He has a lot of questions and that's why he waters her to see if she grows up soon and gives her answers. From the earth a couple of leaves are peeked out, Anacleta takes care of them and tells them stories" ...